Effectiveness of psycho-education intervention program on quality of life, coping strategies and psychological distress among jordanian women diagnosed with breast cancer - Younis, Murad Abdulraheem Abdelrahman (2021)
The diagnosis of breast cancer is distressing and devastating events that may befall women. It is considered a major stressful event that threats all aspects of woman's' life and can regarded as a challenge to women’s basic values, beliefs and goals, life functions and threatening their sense of identity. At the time of diagnosis, the patients face unmet knowledge needs and they express the greatest need to speak with someone who has experienced and overcame the same disease. In this study, related to knowledge and sharing experience that will be provided to the breast cancer patients with aim of enhance the reappraisal of stressful situation that reduce the psychological distress, and promote quality of life through enhance coping strategy. The objective of this study was to determine the effectiveness of psycho-education intervention program on quality of life, coping strategies, psychological distress among Jordanian women diagnosed with breast cancer.A randomized controlled trial, double-blind study was conducted with 200 participants from Al-Bashir Hospital in Amman city. The participants include all Jordanian women in aged 20-65 years and had diagnosis of breast cancer in stage 0, I, II or III. The participants who met the eligibility criteria was selected randomly after which they were evenly randomized using randomly generated permuted blocks of equal sizes into one of either the intervention or control group. The intervention group then underwent two-day health education session on breast cancer, which was strictly guided by the Fawzy Fawzy module. This comprised of four components: 1) health education; 2) coping skills training; 3) stress management; and 4) psychosocial support. The outcomes were measured by using EORTC QLQ-C30 and QLQ-BR23 questionnaires to assess the quality of life, Brief COPE scale to assess coping strategy, and Hospital Anxiety Depression Scale (HADS) to assess the anxiety and depression among Jordanian breast cancer women. Generalised Linear Mixed Models was conducted to evaluate the effect of the intervention adjusted for confounding variables. The results showed that the intervention group was significant in increasing the quality of life: QLQ-C30 (=0.137, P=0.006), QLQ-BR23 (=0.190, P=0.001); adaptive coping skills (=0.921, P<0.001), and decreasing anxiety score (=-0.378, P<0.001) and depression score (=-0.525, P<0.001) compared to the control group. The intervention was effective in positively affecting the QOL, adaptive coping strategies and psychological distress. It is recommended for adoption as part of routine health education given at oncology clinics in Jordan.